NAVAJO NATION PRESIDENTIAL ELECTORAL COMPETITION: The Challenges for Indigenous Religious Freedom in Canada Today (Canadian Journal of Native Studies, 2026)
AbstractFindings presented in this study show that competition in the four mostrecent Navajo Nation Presidential General Elections, the second roundin the non-partisan majority run-off electoral system, reflect choicesmade about specific candidates, with concentrations of support for JonathanNez and opposition to Joe Shirley Jr., rather than a ‘nationalizing’trend toward reduced competition at the national and chapter levels ofgovernment. Voter support for repeat candidates in the Primary Electionor first round contests is revealed to be weak. However winningcandidates in the General Election perform well in chapters where theyperformed well in the Primary Election.